Immune Thrombocytopenia after Allogeneic Stem Cell Transplantation: Case Report and Brief Overview of Treatment Strategies - Isacco Ferrarini; Gloria Turri; Dino Veneri; Cristina Tecchio; Achille Ambrosetti (Journal of Hematology and Oncology Research, 2016)
Immune thrombocytopenia (ITP) is a rare but well-recognized post-allogeneic hematopoietic stem cell transplant (HSCT) autoimmune complication for which a standard treatment approach is lacking. Herein we report on an adult patient affected by high-risk acute myeloid leukemia (AML) who developed a post-HSCT ITP. Due to the refractoriness to first-line therapies the patient underwent the thrombopoietin (TPO) mimetic Eltrombopag obtaining the ITP resolution. We also discuss the clinical course of ITP in post-HSCT setting and pros and cons of different therapeutic strategies, focusing on the emerging role of TPO mimetics.